(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This research is aimed at determining the level of financial literacy of young people and analyzing the factors that influence their financial understanding. During the study, a survey was carried out through Google forms, drawing up 15 questionnaires to determine the financial understanding of students, teachers, schoolchildren and other professions. The results of the survey focused on identifying the respondents ’ views on financial freedom, success, wealth and investment, as well as developing recommendations necessary to improve their financial knowledge.